Online Learning during the COVID-19 Pandemic: An Experience of Catholic Religion Teacher - Amon, Lorensius; Jela, Kristina; Margareta, Margareta; Anggal, Nikolaus (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This paper reports a qualitative study on Catholic religious learning during the COVID-19 pandemic in East Kalimantan Province, Indonesia. Studies on online learning have actually been done a lot, however, especially in Catholic religious learning, it seems that it is still rare. The development of the results of this study was obtained from interviews with Catholic religious teachers about learning patterns in their schools. Data were collected through a qualitative approach to enable the collection of substantial descriptive data to form the basis for the design of the conceptual framework. The results of this study show that teachers have carried out their learning well by integrating learning and support, namely schools, teachers, and parents. Through this integration, students can achieve an essential Catholic moral and spiritual experience. Students gain positive and meaningful experiences about family life, especially through learning experiences with their parents or guardians.